Pengaruh Inovatif Work Behavior terhadap Kinerja Karyawan dengan Keterlibatan Kerja Sebagai Variabel Mediasi : Studi pada Badan Penanggulangan Bencana Daerah Kota Batu - Hernandes Elisa Putra; Adya Hermawati; Choirul Anam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the rapidly changing digital and global era, organizations are required to be adaptive and innovative to survive and compete sustainably. Employee performance is one of the strategic factors in supporting organizational success. This research is motivated by the urgency of improving performance through innovative work behavior (IWB) and work engagement, which are considered two key elements in addressing the challenges of modern organizations. The main objective of this study is to analyze the effect of IWB on employee performance and evaluate the mediating role of work engagement in this relationship. This study uses a quantitative approach with the Structural Equation Modeling Partial Least Square (SEM-PLS) method, and was conducted on employees of the Batu City Regional Disaster Management Agency (BPBD). The results of the analysis indicate that IWB has a positive and significant influence on work engagement and employee performance. In addition, work engagement is also proven to act as a partial mediator that strengthens the relationship between IWB and performance. This means that the higher the innovative behavior of employees, the higher their engagement in work, which ultimately has a positive impact on performance improvement. These findings enrich the theoretical literature, particularly supporting theoretical frameworks such as Social Exchange Theory, Self-Determination Theory, Job Demands-Resources Model, and Conservation of Resources Theory. Practical implications of this research suggest that organizations need to create a work environment that supports innovative behavior and enhances employee work engagement by providing autonomy, recognition, and opportunities for self-development. This research suggests further studies to explore other contextual factors, such as organizational culture, transformational leadership, and supervisor support, which have the potential to strengthen the relationship between IWB, work engagement, and employee performance in various organizational sectors.